Study of the dynamics of catalase activity in blood and liver tissue of old rats at experimentally induced dyslipoproteinemia against the background of mechanical damage to the skeletal muscle - O. N. Pavlova; O. N. Tulaeva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
The population of Russia, as well as the population of the developed countries, is steadily aging. Atherosclerosis in elderly patients is most often manifested by acute and severe forms, such as heart attack and stroke. With age, there is an intensification of oxidative processes and a decrease in the activity of antioxidant enzymes. Creation of experimental model of dislipoproteinemia followed by skeletal muscle mechanical trauma in rats will allow to reveal the regularities of oxidative homeostasis changes and use the data obtained in therapy of elderly patients with atherosclerosis.Aim of the investigation: to study the dynamics of catalase activity in blood and tissues of aged rats under oxidative stress caused by modeling of dyslipoproteinemia followed by mechanical injury of skeletal muscle.Materials and methods. The investigation was performed on 120 white non-pedigreed healthy male rats aged 24 months (old rats) weighing 230–250 grams. All animals were divided into four groups, 30 rats in each. The animals in the first group were intact rats, to which no treatment was applied. The animals in the second group had a mechanical dissection in the middle third of the hind limb calf muscle. Animals in groups one and two were on a standard vivarium diet and had free access to water and food. The animals of the third and fourth groups were subjected to simulated dyslipoproteinemia for 63 days and received a high-carbohydrate and high-fat diet with an increased fat content up to 30% by weight of dry matter and replacement of drinking water by a 20% fructose solution. After a certain period of time, the animals in the fourth group underwent injuries of the middle third of the hind limb calf muscle.Conclusions. Mechanical trauma combined with dyslipoproteemia in aged rats is characterized by intense oxidative stress and leads to the decrease of activity of the antioxidant enzyme catalase in blood and liver tissues.